A 24-year-old woman with rapidly progressing vision loss - Modabber, Milad; Gupta, vasudha; Rodriguez, Amadeo R. (Digital Journal of Ophthalmology, 2017)
A 24-year-old woman was referred to the Department of Ophthalmology, McMaster University, Hamilton, Ontario, for urgent neuro-ophthalmological evaluation following rapidly progressive vision loss and a 3-week history of constant, severe headache. The patient was otherwise healthy with no past medical or ophthalmic history. She had no previous history of such episodes, and she denied any history of recent trauma or infection. Her body mass index was 31, with a reported weight loss of 10 kg over the last 4 months. She was on oral contraceptives but denied taking any other medication.